Дистанційне навчання майбутніх фармацевтів в умовах воєнного стану (досвід медичних ЗВО України) - Лисенко, Т. А.; Панченко, Світлана Валеріївна; Привалко, Е. Г.; Калібабчук, В. О. (My University, 2023)
Мета цієї роботи полягає в оцінюванні можливостей системи дистанційного навчання для закладів вищої медичної освіти, виявлення переваг і вирішення проблем, які впливають на її інтеграцію в медицині. Результати дослідження показали, що в умовах війни дистанційне навчання дозволило медичним та фармацевтичних студентам завершити програми та скласти фінальні іспити, проте, у зв’язку зі специфікою галузі, дистанційне навчання замінили гібридним. Платформи дистанційного навчання Zoom, Google Meet та Moodle є дієвими для медичної освіти, проте, зважаючи на особливості галузі, можуть слугувати більше в якості корисного доповнення для очного навчання. The purpose of this paper is to assess the capabilities of the distance learning system for higher medical education institutions, identify the benefits and solve the problems that affect its integration into medicine. The results of the study showed that during the war, distance learning allowed medical and pharmaceutical students to complete their programs and pass their final exams, but due to the specifics of the industry, distance learning was replaced by hybrid learning. Distance learning platforms such as Zoom, Google Meet, and Moodle are effective for medical education, but given the specifics of the industry, they can serve more as a useful supplement to face‐to‐face learning. A distance education system is a form of education in which teachers and students are physically separated, inseparable from the use of information and communication technologies. The COVID‐19 pandemic has forced education systems around the world, to look for new methods of teaching and learning, such as distance learning. The development of informational technologies and their application in education has created a new area for the teaching‐learning system. In addition to the use of tools (laptop, smartphone, tablet), the Internet is now the environment for a virtual classroom that creates or simulates presence in a state of absence. Such learning becomes quite flexible through the use of learning platforms. It is important to note that online learning in higher medical education does not replace face‐to‐face teaching. The course can be delivered synchronously via audio, video, or web conferencing, or asynchronously via online discussion forums, blogs, messaging, and email. For higher medical education institutions, the transition to distance learning with the use of learning platforms has become only a temporary prospect given the specifics of medical education. Distance learning was intensively used during the COVID‐19 pandemic, and then the war on 24 February 2022 forced educational institutions to react and return to it. The evaluation of teaching systems includes steps related to the program being taught and its objectives, resources, process, tools used, and the teaching system. Such an assessment requires a survey of stakeholders (school/university administration, students, as well as learning outcomes and community needs.
Distance learning of future pharmacists and pharmacy technicians during martial law (experience of medical higher education institutions in Ukraine)
Keywords: дистанційне навчання; гібридне навчання; галузь фармації; distance learning; hybrid learning; pharmaceutical industry; Мoodle